Lower Adiponectin Levels at First Trimester of Pregnancy Are Associated With Increased Insulin Resistance and Higher Risk of Developing Gestational Diabetes Mellitus - Marilyn Lacroix; Marie‐Claude Battista; Myriam Doyon; Julie Ménard; Jean‐Luc Ardilouze; Patrice Perron; Marie‐France Hivert (2013)
OBJECTIVE To evaluate the associations between adiponectin levels and 1) the risk of developing gestational diabetes mellitus (GDM), and 2) insulin resistance/sensitivity, β-cell function, and compensation indices in a prospective cohort representative of the general population of pregnant women. RESEARCH DESIGN AND METHODS We performed anthropometric measurements and collected blood samples at 1st (6–13 weeks) and 2nd (24–28 weeks) trimesters. Diagnosis of GDM was made at 2nd trimester based on a 75-g oral glucose tolerance test (International Association of the Diabetes and Pregnancy Study Groups criteria). Insulin was measured (ELISA; Luminex) to estimate homeostasis model assessment of insulin resistance (HOMA-IR), β-cell function (HOMA-B), insulin sensitivity (Matsuda index), insulin secretion (AUCinsulin/glucose), and β-cell compensation (insulin secretion sensitivity index-2). Adiponectin was measured by radioimmunoassay. RESULTS Among the 445 participants included in this study, 38 women developed GDM. Women who developed GDM had lower 1st-trimester adiponectin levels (9.67 ± 3.84 vs. 11.92 ± 4.59 µg/mL in women with normal glucose tolerance). Lower adiponectin levels were associated with higher risk of developing GDM (OR, 1.12 per 1 µg/mL decrease of adiponectin levels; P = 0.02, adjusted for BMI and HbA1c at 1st trimester). Adiponectin levels at 1st and 2nd trimesters were associated with HOMA-IR (both: r = −0.22, P < 0.0001) and Matsuda index (r = 0.28, P < 0.0001, and r = 0.29, P < 0.0001). After adjustment for confounding factors, we found no significant association with HOMA-B and AUCinsulin/glucose. CONCLUSIONS Pregnant women with lower adiponectin levels at 1st trimester have higher levels of insulin resistance and are more likely to develop GDM independently of adiposity or glycemic measurements.